A Nilometer from Graeco-Roman Thmouis. (7th September 2022) - Silverstein, Jay E; Littman, Robert J; Bagdi, Stacey Anne; Eltalhawy, Elsayed F; Mashaly, Hamdy Ahmed; Mohamed, Emad Hassan; Gabr, Mohamed
Abstract : In 2010, a construction project for a new water pumping station on the west side of Tell Timai (Egyptian Delta) encountered a limestone structure. This discovery triggered a salvage excavation that exposed a rare example of a well-preserved Delta nilometer. The architectural features of the nilometer reveal some specific and even unique adaptations consonant with the hydrological situation of the Graeco-Roman city of Thmouis. Unlike other examples of nilometers, an aqueduct runs from the north, spilling into the stairwell leading down into the stilling well. A dam stone in the aqueduct appears to have regulated the release of water. The nilometer was also articulated with an adjacent hill by a staircase. Folk tradition memorialised the stair and nilometer location in local fertility and healing rituals performed during Nile flood-related festivals; this tradition preserved the sacred space long after the nilometer and its associated architecture were buried and forgotten. The multifaceted role of the Thmouis nilometer in the cultural and economic life of the city and nome carries wider implications for the political organisation of the nome and the dynamic between syncretic forces and imperial appropriation in Graeco-Roman Egypt. Here we review the shape, function, archaeological context, ideological significance and hydrography of the nilometer and consider the implications of the nilometer for the history of the Mendesian nome and its sacred relationship with the Nile River.